Duties and Functions of the Bone Resort Police in Overcoming Narcotics Abuse as a Rescue Effort Bone's Young Generation - Mukhawas Rasyid (Universitas Serambi Mekkah, 2022)
This study aims to describe how the duties and functions of the police in overcoming criminal acts of narcotics abuse in Bone Regency. How are the obstacles to overcoming and eradicating narcotics crimes in the jurisdiction of the Bone District Police. This research was conducted at the Bone Resort Police Office. The types of data are primary and secondary data, primary data obtained through direct interviews with competent respondents, in this case the Bone Police Investigator of the Narcotics Unit, as well as the perpetrators of the Crime of Narcotics Abuse in Bone Regency. Secondary data was obtained through literature from various books, legal regulations, documents and other written data which were considered related to this research. The results of the study indicate that (1) the duties and functions of the Police in overcoming criminal acts of narcotics abuse in Bone Regency have been carried out in accordance with the applicable laws and regulations, namely the Law of the Republic of Indonesia Number 2 of 2002 concerning the National Police of the Republic of Indonesia and Law No. 35 of 2009 concerning narcotics. (2) Barriers to overcoming and eradicating narcotics crime in the jurisdiction of the Bone District Police are in addition to the limited number of personnel in the Bone Resort Narcotics unit, as well as the lack of human resource capabilities possessed by the apparatus in the Information Technology (IT) field, so that it affects the making of files. cases and and collection of evidence. as well as the lack of funds for the police in conducting outreach to the community.